Factors Associated with Pulmonary TB Patients' Self Efficacy in Undergoing Treatment: Faktor-faktor yang Berhubungan dengan Self Efficacy Pasien TB Paru dalam Menjalani Pengobatan - Nurmalisa, Baiq Emy (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2022)
Background: Pulmonary tuberculosis is a direct infectious disease caused by bacteria. Efforts to control pulmonary TB with the DOTS strategy have been implemented in various countries. In addition to the DOTS strategy, self-efficacy or confidence in the patient is the most important factor in controlling pulmonary TB. Self efficacy is an individual's belief in managing certain behaviors to achieve healing. Self efficacy is influenced by one's own experience, observation of others, verbal persuasion, and physiological evaluation. The purpose of this study was to determine the relationship between self-experience, observation of others, verbal persuasion, physiological evaluation and self-efficacy in pulmonary TB patients undergoing treatment in the UPTD area of ​​the Tangeban Health Center. Methods: This study uses an analytic design through a cross sectional approach with a sample of 33 people, obtained from the total sampling. Data was collected using a questionnaire and analyzed using the chi-square test. Results of the analysis of research data obtained a correlation value between one's own experience and self-efficacy with a significance level of 0.024 (α<0.05), observation of other people with self-efficacy with a significance level of 0.013 (α<0.05), verbal persuasion with self efficacy with a significance level of 0.031 (α<0.05), and the results of the correlation value between physiological evaluation and self efficacy with a significance level of 0.027 (α<0.05). Conclusion there is a significant relationship between self-experience, observation of others, verbal persuasion and physiological evaluation with the self-efficacy of TB patients.